Problem based training on protection of women and children from domestic violence for other hospital personnel : participant's manual - Philippines. Department of Health (Manila : Department of Health)
Participant's manual
Keywords: Child Welfare; Child Protective Services; Women's Rights; Domestic Violence; Teaching Materials